The Effect of Anise Oil (Pimpinella anisum L.) On Broiler Performance - Ciftci, Mehmet; Guler, Talat; Dalkilic, Bestami; Ertas, O. Nihat (International Journal of Poultry Science, 2005)
This study was conducted to determine the use of anise oil in broiler nutrition as a natural growth promoting substance instead of antibiotics. Different levels of anise oil were added to a standard diet, to determine its effect on feed intake, daily live weight gain and feed conversion ratio compared to control and antibiotic groups. Two hundred day-old broilers (Ross-308) were divided into groups of 40 birds each and randomly assigned to the five treatment diets. Each treatment has four replicates. Experimental groups were as follow: A Control group with no anise oil or antibiotic added, a 100 mg/kg Anise oil group, a 200 mg/kg Anise oil group, a 400 mg/kg Anise oil group with corresponding inclusion levels, and an antibiotic group with 0.1% added antibiotic (Avilamycin). The feed intake was similar in groups (p>0.05). The highest (p< 0.01) daily live weight gain was observed on the 400 Anise oil group (70.35 g) and followed by Antibiotic group (65.84 g), 100 Anise oil group (62.57g), 200 Anise oil group (62.47 g) and control group (61.30 g). The addition of 400 mg/kg anise oil to the diets was improved daily live weight gain by approximately 15% compared to the control group. This improve was remained 7 % level in antibiotic group. Additionally, the addition of 400 mg/kg anise oil to the diets was improved daily live weight gain by approximately 6.5% compared to the antibiotic group. The addition of 400 mg/kg anise oil to the diets was improved feed conversion ratio by approximately 12 % compared to the control group. This improve was remained 7 % level in antibiotic group. Additionally, the addition of 400 mg/kg anise oil to the diets was improved feed conversion ratio by approximately 6 % compared to the antibiotic group. 7. In conclusion, anise oil could be considered as a potential natural growth promoter for poultry.